‘‘Practices and factors affecting on-site medical equipment maintenance at Wau Teaching Hospital, South Sudan’’ - Natale Massimino Ucin; Manassé Nimpagaritse; Shital Mahindra Maru; Mulatedzi Makhado; Shiferaw Mitiku Tebeka (BMC Public Health)
Abstract Background of the study Along with developments in the clinical domain, medical equipment is becoming more sophisticated, and it needs to function at peak efficiency. In this case, hospitals should priorities the prompt and effective maintenance of life-saving equipment. The purpose of the study was to determine medical equipment maintenance practices, to find out an important factor that influences on-site medical equipment maintenance practices and to suggest possible areas for improvement. Method This was a cross-sectional descriptive quantitative research design conducted from November 2022 to February 2023. Data were collected using self-administered structured questionnaires. A sample size of 212 respondents was determined using Slovin’s Formula (N/ 1+ Ne²) from a population size of 450. A convenience sample technique was used to select the participants. An exploratory factor analysis was performed to test the inter-relationship between variables, Bartlett’s test of sphericity(p = 0,000) indicated a significant correlation, The Kaiser-Meyer- Olkin measure of sample adequacy was 0.800, and this value indicated the appropriateness of the data. A desk review and observational checklist were used. Results In this study, a descriptive statistic was performed under three objectives: the overall grand mean value of medical equipment maintenance practice was 2.11, and it showed the practices were uninfluential; the overall grand mean value of factors influencing medical equipment maintenance practices was 3.61, and the identified factors were influential; and lastly, the overall grand mean value of root causes of medical equipment maintenance failures was 3.565, and the identified factors were found to be influential factors. Conclusions The findings showed that medical equipment maintenance practice was a weekly practice; factors influencing medical equipment maintenance practice and the root causes of medical equipment maintenance failure were identified as influential factors. Corrective maintenance and outsourcing were the main maintenance practices observed, along with a lack of biomedical personnel, inadequate information aboutdevices, a lack of periodical inspection and prevention, design and implementation, and inappropriate medical equipment.